2019
DOI: 10.1002/jsfa.9865
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endophyte Phomopsis liquidambari biodegrades soil resveratrol: a potential allelochemical in peanut monocropping systems

Abstract: BACKGROUND Most allelochemicals are secondary products released from root excretions or plant residues that accumulate in continuous cropping systems and cause severe decline in peanut yield. Resveratrol is a plant‐derived stilbene that is released from peanut residues and accumulates in the soil; however, its allelopathic effects on peanut production are overlooked. Effective management solutions need to be developed to relieve allelopathy caused by soil resveratrol. Here, the biodegradation of resveratrol by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…It was reported that allelochemicals from root exudates or decomposants of crops could induce autotoxicity and were closely related to soil sickness (Asaduzzaman & Asao, 2012;Huang et al, 2013). These allelochemicals accumulated with monocropping period, but not to high levels (Yang et al, 2015;Li et al, 2014a), possibly due to interactions between allelochemicals and soil microbes (Li et al, 2014a;Wang et al, 2019). Based on the analyses, the increased bacterial taxa that could promote plant growth or degrade potential soil allelochemicals should be closely related to soil remediation and may have potential application to relieve soil sickness under peanut monocropping.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that allelochemicals from root exudates or decomposants of crops could induce autotoxicity and were closely related to soil sickness (Asaduzzaman & Asao, 2012;Huang et al, 2013). These allelochemicals accumulated with monocropping period, but not to high levels (Yang et al, 2015;Li et al, 2014a), possibly due to interactions between allelochemicals and soil microbes (Li et al, 2014a;Wang et al, 2019). Based on the analyses, the increased bacterial taxa that could promote plant growth or degrade potential soil allelochemicals should be closely related to soil remediation and may have potential application to relieve soil sickness under peanut monocropping.…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathy has also been directly linked to continuous cropping disorder. There are some studies on continuous cropping in rice (Hameed et al, 2019), peanut (Wang et al, 2019), tobacco (Ren et al, 2017), and ginseng (Xiao et al, 2019) which have found that high concentrations of allelopathic substances secreted by roots can produce an autotoxic effect. High levels of toxic substances secreted by sugar beet's root are known to cause root rot, the blight of sugar beet, brown spot, and other diseases in sugar beets or other crops (Khorassani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol is a naturally occurring nonflavonoid polyphenol compound, which is widely present in natural plants such as grape, knotweed, cassia seed, and peanut [ 17 ]. Previous studies have reported that resveratrol has various biological effects such as anti-inflammatory, antioxidant, and antitumor [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%